2011
DOI: 10.2214/ajr.10.4271
|View full text |Cite
|
Sign up to set email alerts
|

Body CT During Pregnancy: Utilization Trends, Examination Indications, and Fetal Radiation Doses

Abstract: Growth of CT during pregnancy reflects the trend of increased CT utilization in the general population. Avoiding use of CT in pregnant patients with suspected appendicitis would significantly decrease fetal radiation exposure. Abdominopelvic CT during pregnancy should be carefully planned and monitored so as not to exceed the fetal radiation dose for negligible risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 17 publications
0
32
0
2
Order By: Relevance
“…Previous literature states that additional CT imaging can reduce the negative appendectomy rate during pregnancy [11,16]. However, ionizing radiation is a significant disadvantage of CT because it is a potential hazard to the developing fetus [11,17]. When the exposure to radiation during a CT scan is less than 500 mGy, no increase in adverse pregnancy outcomes is seen, but the risk for childhood cancer is estimated to increase by 0.1% following a fetal radiation dose of 100 mGy [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature states that additional CT imaging can reduce the negative appendectomy rate during pregnancy [11,16]. However, ionizing radiation is a significant disadvantage of CT because it is a potential hazard to the developing fetus [11,17]. When the exposure to radiation during a CT scan is less than 500 mGy, no increase in adverse pregnancy outcomes is seen, but the risk for childhood cancer is estimated to increase by 0.1% following a fetal radiation dose of 100 mGy [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, ionizing radiation is a significant disadvantage of CT because it is a potential hazard to the developing fetus [11,17]. When the exposure to radiation during a CT scan is less than 500 mGy, no increase in adverse pregnancy outcomes is seen, but the risk for childhood cancer is estimated to increase by 0.1% following a fetal radiation dose of 100 mGy [17]. Therefore, given the potential teratogenic and carcinogenic effects of ionizing radiation on the developing fetus, diagnostic medical imaging should be avoided where possible in a pregnant patient and used only when absolutely necessary [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…115 Pulmonary CTA and perfusion scintigraphy are both the recommended imaging procedures of choice of the Fleischner Society and the Task Force for the Diagnosis and Management of Acute Pulmonary Embolism of the European Society of Cardiology. [120][121][122][123] One study reported similar radiation doses to the fetus on using 16-slice pulmonary CTA, V/Q scintigraphy, or perfusion scintigraphy alone. 119 There is no clear evidence supporting the superiority of either pulmonary CTA or perfusion scintigraphy as the preferred choice in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…International Commission on Radiological Protection guidelines state that fetalradiation doses less than 100mGy should not be a reason for terminating the pregnancy[27]. A recent publication estimated fetal radiation doses from abdominal-pelvic CT between 8.6 and 23.4mGy/100mAs, depending on scanner, kVp, and beam collimation[28]. This is a range in which there is real concern for effects on the fetus.…”
Section: Pregnancy and Diagnostic Ctmentioning
confidence: 99%